(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article examines the scientific views of strengthening the deposit base of commercial banks, analyzing the current state of the deposit base of commercial banks in our country and the influence of internal and external factors on the expansion of deposits, and also considers ways to strengthen and expand the resource base of banks.